Uptown, downbeat: Mobility, masculine self-fashioning and occupations of space in African American urban narrative discourse (1962--1972) - Godin, Julie Cecilia (University of Ottawa (Canada), 2007)
This project examines neglected African American urban narratives produced by male writers from the mid-1960s to mid 1970s, in order to document and interrogate how the production of subjectivities and masculinities are shown to intersect, in these works, with vectors of mobility and modalities of spatial occupation. The study begins with the mobile culture of the Blues, and highlights sophisticated Blues stylings to trace the operation of a language of vagrancy---a discourse of malleability that opens the masculine subject to multiplicity and detachment. It then examines the spectacular, transient, and materialistic player of the urban "barbershop books," and details, in Robert Beck's Pimp: The Story of My Life, and in Donald Goines's Whoreson and Daddy Cool, the exhausting, destructive experiments that permit display and re-invention on the "street." This vision is supplemented with urban texts that address the subject's inhabitation of densely peopled space and the enigma of fleshly occupation in urban arrangements of troubling proximity. The work examines Chester Himes's Blind Man With a Pistol, Eldridge Cleaver's Soul on Ice, and Down these Mean Streets, by Piri Thomas, in order to consider the excessive traces of bodily inhabitation and the provocative yet repulsive closeness of an enigmatic neighbour. It then turns to George Cain's poetic Blueschild Baby and Robert Beck's Mama Black Widow, to interrogate how these texts address the death drive and delineate the possibility of inhabiting the ruined ghetto with an insistent impulse to endure and resist. Finally, the work considers two texts, Robert Deane Pharr's S.R.O. and Herbert Simmons's Man Walking on Eggshells, in which segmented space, proliferating multiplicities, and emergent subjects invite a reading informed by the vocabularies of Gilles Deleuze. The project ends by reading the urban subject as a stylish, agile principle of released motion, creative doubt and active engagement with differences and potentialities.
Keywords: Black Studies.; Literature, Canadian (English).